School Smoking Policies and Health Science Students' Use of Cigarettes, Shisha, and Dipping Tombak in Sudan - El Amin, Salma El Tayeb (Frontiers in Public Health, 2019)
Abstract The relationship between school policies and students’ tobacco use is ambiguous, and little is known about low- and middle-income countries. This study was designed to assess the existence of schools’ smoking policies, students’ exposure to residential smoking, and their relationships with Health Science students’ (HSS) tobacco use (cigarettes smoking, shisha use, tombak-dipping and tobacco use on school premises). A cross-sectional survey was carried out using a modified self-reported questionnaire, originally developed by WHO, among a representative sample of 1590 third-year HSS from 25 schools drawn from 13 universities, with probability proportional to enrollment of schools and third-year students, using three-stages sampling techniques. The response rate was 100% for schools and 68% for students. A multilevel analysis was performed by nesting student-level in school-level variables. Results from the adjusted models revealed that, when students reported awareness of smoking restriction, they were more likely to be current smokers (OR = 2.91; 95% CI: 1.68 to 5.02; p = 0.021) and shisha users (OR = 2.17; 95% CI: 1.54 to 3.06; p = 0.021). Results from additional analysis performed among tobacco users only, showed increased risk of smokers and tombak dippers who smoked or dipped on school premises (OR = 2.38; 95% CI: 1.34 to 4.25; p = 0.003, OR = 2.60; 95% CI: 1.22 to 5.56; p = 0.013, respectively). Current smokers (OR = 3.12; 95% CI: 1.98 to 4.92; p = ≤ 0.001), ever smokers (OR = 1.66; 95% CI: 1.31 to 2.10 p = ≤ 0.001) and shisha users (OR = 1.73; 95% CI: 1.36 to 2.21; p = ≤ 0.001) were exposed to residential smoking on one or more days during the previous 7 days. High percentages of those who used any kind of tobacco products reported being aware of school smoking policies, indicating no clear evidence that school smoking policies had an impact on use of any of the mentioned tobacco products. The lack of compliance with school policies shows the need for further policy enforcement and sustainability, taking into account the effect of residential smoking and social influences.